Decolonization of Arctic Library and Archives Metadata (DALAM) Thematic Network Update: April 2023 - Campbell, Sandra M (Zenodo, 2023)
This is a published update of the activities of the University of the Arctic Thematic Network on Decolonization of Arctic Library and Archives Metadata (DALAM), issued months prior to the final endorsement of the network by University of the Arctic.